1990
DOI: 10.2527/1990.6841061x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological relationships between microbiological status and dietary copper levels in the pig

Abstract: Ten germ-free pigs and 10 conventionally reared pigs were fed one of two nutritionally balanced diets containing either 16 ppm Cu (basal) or 283 ppm Cu (high-Cu) to evaluate the physiological relationships between Cu and microbiological environment. Germ-free pigs tended to have higher ADG and average daily feed intake (ADFI) than conventionally reared pigs. Feeding the high-Cu diet tended to reduce ADG and ADFI in germ-free pigs but it increased ADG and ADFI in conventionally reared pigs. Hemoglobin and hemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
48
3
7

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 0 publications
9
48
3
7
Order By: Relevance
“…In accordance with these findings we have also found that copper affects the composition and activity of the microbiota in the gastrointestinal tract of weaned pigs ( Figure 5). Evidence that copper accomplishes its growth promoting effect through the microbiota is further supported by the results of Shurson et al (1990), which showed that high Cu (283 ppm) tends to increase daily growth rate and feed conversion rate in conventional pigs but decreases them in germ-free pigs. Shurson et al (1990) also found that high Cu generally reduces villus height and width and crypt depth in germ-free pigs, whereas it increases these parameters in conventional pigs.…”
Section: St Si1 Si2 Si3 Cae Co1 Co2 Rec St Si1 Si2 Si3 Cae Co1 Co2 Recsupporting
confidence: 52%
See 1 more Smart Citation
“…In accordance with these findings we have also found that copper affects the composition and activity of the microbiota in the gastrointestinal tract of weaned pigs ( Figure 5). Evidence that copper accomplishes its growth promoting effect through the microbiota is further supported by the results of Shurson et al (1990), which showed that high Cu (283 ppm) tends to increase daily growth rate and feed conversion rate in conventional pigs but decreases them in germ-free pigs. Shurson et al (1990) also found that high Cu generally reduces villus height and width and crypt depth in germ-free pigs, whereas it increases these parameters in conventional pigs.…”
Section: St Si1 Si2 Si3 Cae Co1 Co2 Rec St Si1 Si2 Si3 Cae Co1 Co2 Recsupporting
confidence: 52%
“…Evidence that copper accomplishes its growth promoting effect through the microbiota is further supported by the results of Shurson et al (1990), which showed that high Cu (283 ppm) tends to increase daily growth rate and feed conversion rate in conventional pigs but decreases them in germ-free pigs. Shurson et al (1990) also found that high Cu generally reduces villus height and width and crypt depth in germ-free pigs, whereas it increases these parameters in conventional pigs. 250 ppm Cu (as copper sulphate) has also been shown to stimulate intestinal lipase and phospholipase A 2 activities, leading to an improvement of dietary fat digestibility in weaning pigs (Luo et al, 1996), and to increase protein utilisation, most probably through activation of pepsin activity (Kirschgessner et al, 1976).…”
Section: St Si1 Si2 Si3 Cae Co1 Co2 Rec St Si1 Si2 Si3 Cae Co1 Co2 Recsupporting
confidence: 52%
“…Reduced crypt depth and increased villus length agree with the previous observations in germ-free pigs (Kenworthy, 1970;Thompson, and Trexler, 1971;Wostmann, 1975;Shurson et al, 1990;Shirkey et al, 2005). In the present study villi were the longest in the jejunum and shortest in the duodenum and ileum, whereas crypt depth was shortest in the jejunum and deepest in the duodenum throughout the observation period (Figures 5 and 6).…”
Section: Discussionsupporting
confidence: 82%
“…Cu supplementation decreased crypt depth, which is in agreement with Hedemann et al (2006) who evaluated the effect of dietary Cu and Zn during the 14-day post weaning period in pigs weaned at 28 days of age. However, this result was in contrast to previous studies showing increased crypt depths (Shurson et al 1990) or no effect of higher dietary Cu intake on crypt depths (Radecki et al 1992). Perhaps CS-Cu could increase the amount of readily available nutrients, and thus improve villus development and repair.…”
Section: Discussioncontrasting
confidence: 56%
“…In the current study, Cu supplementation increased villus height, which was in agreement with Shurson et al (1990) and in contrast to previous studies reporting no effect of high Cu supplementation on villus height (Radecki et al 1992;Hedemann et al 2006). It is well known that in piglets villus atrophy and crypt hyperplasia occur after weaning (Xiong et al 2015).…”
Section: Discussioncontrasting
confidence: 47%